UNVEILING THE DYNAMICS OF SEARCH ENGINE OPTIMIZATION (SEO): STRATEGIES, CHALLENGES AND FUTURE TRENDS IN DIGITAL MARKETING (IITM Journal of Business Studies, 2025)
This paper addresses the concept of Search  Engine Optimization (SEO), which is essential  in increasing the exposure of a website and  consequently making it more visible to users.  SEO efforts are grouped as on-page, off-page,  and technical SEO. On-page SEO includes  optimizing the content, adding title, meta,  and image tags, and adjusting the URLs of  target websites. Promoting domain authority  through backlinking, competitor analysis,  and link-building strategies is called off-page  SEO. Technical SEO is all about enhancing  mobile accessibility, XML sitemap, robots. txt, and the security of a website so that search  engines can crawl and index it more effectively.  In order to capture the attention of search  engines, optimizers must be well-versed in its  algorithm ranking factors and ensure that the  page aims to answer a user’s inquiry as well as  target certain phrases that assist with higher  ranking. There is an emphasis on the need  for ethical SEO, and optimizers need to keep  adapting to new algorithm updates if they  want to remain competitive. The discussion of future perspectives raises the introduction of  voice search and AI to digital marketing, which  encourages pursuing deeper research.
Keywords: Search Engine Optimization (SEO); On-Page SEO, Off-Page SEO; Technical SEO; Ethical SEO Practices